2007
DOI: 10.1007/s11248-007-9094-y
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of phospholipid transfer protein (PLTP) in transgenic mice: acute effects of PLTP on lipoprotein metabolism

Abstract: One main determinant in high-density lipoprotein (HDL) metabolism is phospholipid transfer protein (PLTP), a plasma protein that is associated with HDL. In transgenic mice overexpressing human PLTP we found that elevated plasma PLTP levels dose-dependently increased the susceptibility to dietinduced atherosclerosis. This could be mainly due to the fact that most functions of PLTP are potentially atherogenic, such as decreasing plasma HDL levels. To further elucidate the role of PLTP in lipoprotein metabolism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…13 Briefly, 2 constructs were used to generate transgenic mice that allow inducible expression of PLTP: (1) hnRNP-rtTA-SV40, which consists of an improved version of the tetracycline-controlled transactivator rtTA2S-M2 under the control of an hnRNP A2 coding sequence, resulting in rtTAtg mice, and (2) pTet-PLTP-SV40, which consists of the human PLTP cDNA under the transcriptional control of a tetracycline operator and minimal cytomegalovirus promoter (TetO/Pcmv min), resulting in TrePLTPtg mice. Both Tre-PLTPtg mice and rtTAtg mice were crossed into an LDLR Ϫ/Ϫ background (Jackson Laboratory, Bar Harbor, ME, USA).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Briefly, 2 constructs were used to generate transgenic mice that allow inducible expression of PLTP: (1) hnRNP-rtTA-SV40, which consists of an improved version of the tetracycline-controlled transactivator rtTA2S-M2 under the control of an hnRNP A2 coding sequence, resulting in rtTAtg mice, and (2) pTet-PLTP-SV40, which consists of the human PLTP cDNA under the transcriptional control of a tetracycline operator and minimal cytomegalovirus promoter (TetO/Pcmv min), resulting in TrePLTPtg mice. Both Tre-PLTPtg mice and rtTAtg mice were crossed into an LDLR Ϫ/Ϫ background (Jackson Laboratory, Bar Harbor, ME, USA).…”
Section: Animalsmentioning
confidence: 99%
“…6,10 -12 Recently we developed a transgenic mouse model that allows conditional expression of human PLTP. 13 We hypothesize that the physiological effect of an acute increase in plasma PLTP activity differs significantly from the effects seen in mice overexpressing human PLTP innately and life-long and which may have developed compensatory mechanisms. We tested this hypothesis in transgenic mice that conditionally overexpress human PLTP and that are deficient for the LDL receptor.…”
mentioning
confidence: 98%
“…On the contrary, PLTP deficiency results in markedly decreased atherosclerosis by a decrease in the production and levels of apoB-containing lipoprotein, an increase in their vitamin E content, and a decrease in their susceptibility to oxidation [23,26]. It is demonstrated that pronounced higher CETP and PLTP activities can lead to a marked decrease in HDL-C levels that is due to hypercatabolism [1,27-29] and an increase in LDL-C levels that is due to an increase in transfer of CE from HDL to LDL and production of apoB-containing lipoprotein [1,26,30,31]. In tree shrew and beijing duck, low CETP and PLTP activities might cause a low catabolism of HDL-C and a decrease in production of apoB-containing lipoprotein, which led to a relative high plasma level of HDL-C and low level of LDL-C and at last a high resistance to AS.…”
Section: Discussionmentioning
confidence: 99%
“…the double transgene, had significantly higher level of HDL lipids and apoA-I, and had a major increase in prebeta-HDL. Furthermore, a more pronounced increase in PLTP expression resulted in accelerated HDL catabolism and marked decrease in HDL levels along with an increase in prebeta-HDL generation [114-117]. …”
Section: Insights Of Pltp From Animal Studiesmentioning
confidence: 99%